Financial assessment of solar PV system in residential sector of Malaysia [electronic resource] - Mohammad Iman Karamouz, 1985-; Khairulzan Yahya, supervisor; Fakulti Kejuruteraan Awam (2014)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2014